2011
DOI: 10.1007/s10926-011-9336-y
|View full text |Cite
|
Sign up to set email alerts
|

Getting Hired: Successfully Employed People with Disabilities Offer Advice on Disclosure, Interviewing, and Job Search

Abstract: Findings suggest approaches to assist job-seekers to make decisions about disclosing or discussing their disability, present themselves in a straight-forward, disability-positive manner, and find satisfying work based on their skills and interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
91
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(112 citation statements)
references
References 34 publications
3
91
1
1
Order By: Relevance
“…This is problematic given that perceived inequity at work is related to a range of adverse health-related and organizational outcomes (2, 4, 6-9, 11, 42). Although explored in qualitative research (13,43), there has been limited quantitative assessment of fairness and equity among workers with disabilities. Thus, the study represents an important contribution to disability research.…”
Section: Perceived Fairness Of Pay Among People With and Without Disamentioning
confidence: 99%
“…This is problematic given that perceived inequity at work is related to a range of adverse health-related and organizational outcomes (2, 4, 6-9, 11, 42). Although explored in qualitative research (13,43), there has been limited quantitative assessment of fairness and equity among workers with disabilities. Thus, the study represents an important contribution to disability research.…”
Section: Perceived Fairness Of Pay Among People With and Without Disamentioning
confidence: 99%
“…Roberts and Hoff Macan (2006) cited Thomason and Dickey stating this decision-making process can be harder for some individuals with disabilities who do not feel confident in their ability to decide how and when to tell a potential employer about a disability, even though they might have relatively high self-efficacy with interview skills. The choice to disclose or acknowledge one's disability involves complex personal decision making unique to each individual, depending on the visibility, stigma, or level associated with the disability (Jans, Kaye, & Jones, 2012).…”
mentioning
confidence: 99%
“…Jans et al (2012) addressed this in their study, stating that most individuals with mental health issues chose to manage their disability themselves and not mention it to a current or potential employer. A study conducted in 2011 on the pressure surrounding disclosure of mental illness in the workplace concluded that the single cause of non-disclosure was the fear of discrimination, which included being stereotyped and how others might react knowing they had a mental health diagnosis (Peterson, 2011 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations